Retinoic Acid Signaling in Vertebrate Hindbrain Segmentation: Evolution and Diversification - Alice M. H. Bedois; Hugo J. Parker; Robb Krumlauf (Diversity, 2021)
In metazoans, Hox genes are key drivers of morphogenesis. In chordates, they play important roles in patterning the antero-posterior (A-P) axis. A crucial aspect of their role in axial patterning is their collinear expression, a process thought to be linked to their response to major signaling pathways such as retinoic acid (RA) signaling. The amplification of Hox genes following major events of genome evolution can contribute to morphological diversity. In vertebrates, RA acts as a key regulator of the gene regulatory network (GRN) underlying hindbrain segmentation, which includes Hox genes. This review investigates how the RA signaling machinery has evolved and diversified and discusses its connection to the hindbrain GRN in relation to diversity. Using non-chordate and chordate deuterostome models, we explore aspects of ancient programs of axial patterning in an attempt to retrace the evolution of the vertebrate hindbrain GRN. In addition, we investigate how the RA signaling machinery has evolved in vertebrates and highlight key examples of regulatory diversification that may have influenced the GRN for hindbrain segmentation. Finally, we describe the value of using lamprey as a model for the early-diverged jawless vertebrate group, to investigate the elaboration of A-P patterning mechanisms in the vertebrate lineage.